Aspek Dialogis al-Qur'an dalam Perspektif Pendidikan - Mahmud Arif (AL-TAHRIR, 2011)
Some of the thinkers who emerged in the history of thought of Muslims complained of the low response of the Qur’an toward empirical reality and the needs ofcommunity. They were sure that it was because of the tradition of study of the Qur’an that Muslims developed until now is less dialogical approach in addressing the reality, and that the interpretation of studies so far is more dominated by the patterns offiqh, kalam, and mysticism, and only a little to do with the pattern of education. Yet the Qur’an actually views human as the object of education in a long process with the ultimate objective of happiness of the world and the hereafter. This process involves human in an intensive dialogue and it takes time. This paper offers a selection of verses of the Qur’an and then analyses it with a historical approach that the results will be the philosophical basis andfundamental principles of human education efforts to achieve perfect being. This paper concludes that the gradual way of revelation of the Qur’an shows that this holy book presents as a “book of education” that accompanies everyday life of man. Thus the study of the meaning of the verses of the Qur’an with a multidisciplinary approach is a must as a form of attempt to optimize the intake of ”divine nutrition” to human health in living his life.